Compliance to post-exposure prophylaxis among patients attending anti-rabies vaccination clinic in a tertiary health care centre in central India: a cross sectional study - Sastry, Nidhi P.; Deshmukh, Jyotsna S.; Jadhao, Ashok R.; M., Kalaivani; Solanki, Manisha D.; Nitnaware, Vihangi V. (International Journal Of Community Medicine And Public Health, 2023)
Background: Rabies is a fatal but vaccine-preventable disease. Prevention of rabies in exposed individuals is possible by providing them with the proper post-exposure prophylaxis. This study aims to assess the compliance to post-exposure prophylaxis in animal bite cases and factors associated with it. Methods: A cross sectional study was conducted between September 2022 to November 2022 using a predesigned, pretested proforma to interview 300 patients attending anti-rabies vaccination clinic in a tertiary health care centre in central India. Results: Majority of the patients 268 (89.3%) suffered category 3 animal bite and 32 (10.7%) patients suffered category 2 animal bite. 125 (41.7%) patients washed the wound with water, soap and applied antiseptic. 234 (78%) patients completed their last dose of anti-rabies vaccine (ARV) while compliance to Rabies Immunoglobulin (RIG) was seen in 167 (63.3%) patients of all cases requiring it. Out of all the patients who took Equine RIG, 7 (4.5%) showed hypersensitivity reactions. Significant association was found between compliance to ARV with type of animal and status of animal after 10 days; and compliance to RIG with gender, socio-economic status, type of animal and type of wound. Conclusions: Compliance to ARV and RIG in our study was 78% and 63.3% respectively. Major reason for poor compliance to RIG was the price of immunoglobulin. Health education regarding significance of post-exposure prophylaxis is needed among the population.